Hot, flat, and crowded : why we need a green revolution-- and how it can renew America - Friedman, Thomas L. (Farrar, Straus and Giroux, 2008)
Friedman's bestseller "The World Is Flat" has helped millions of readers to see globalization in a new way. Now the author brings a fresh outlook to the crises of destabilizing climate change and rising competition for energy.